Prospective: Evolution of Chinese Medicine to Treat COVID-19 Patients in China - Wu, Jieya; Sun, Baoguo; Hou, Li; Guan, Fulan; Wang, Liyuan; Cheng, Peikwen; Scobell, Sophia; Cheng, Yung-Chi; Lam, Wing (Frontiers in Pharmacology, 2021)
During the outbreak of the novel coronavirus disease (COVID-19), the Chinese government took a series of public health measures to tackle the outbreak and recommended 6 traditional Chinese medicine (TCM) evolved formulas for the treatment. In this prospective article, we will discuss how these six formulas evolved from TCM and what their underlying mechanisms of actions may be by evaluating the historical usage of the component formulas, the potential targeted pathways for the individual herbs used by STAR (signal transduction activity response) database from our laboratory, and the pathogenesis of COVID-19. Five classic categories of herbs in the 6 formulas including “Qing-Re”, “Qu-Shi”, “Huo-Xue”, “Bu-Yi” and “Xing-Qi” herbs are used based on different stages of disease. All five oral formulas build upon the core formula Maxingshigan Decoction (MD) which has anti-inflammatory and perhaps antiviral actions. While MD can have some desired effects, it may not be sufficient to treat COVID-19 on its own; consequently, complementary classic formulas and/or herbs have been added to potentiate each recommended formula’s anti-inflammatory, and perhaps anti-renin-angiotensin system (RAS)-mediated bradykinin storm (RBS) and antiviral effects to address the unique medical needs for different stages of COVID-19. The key actions of these formulas are likely to control systemic inflammation and/or RBS. The usage of Chinese medicine in the six formulas is consistent with the pathogenesis of COVID-19. Thus, an integrative systems biology approach – combining botanical treatments of conventional antiviral, anti-inflammatory or anti-RBS drugs to treat COVID-19 and its complications – should be explored.